Vladas Žukas as a University Lecturer and Researcher - Kaunas, Domas (Knygotyra, 2025)
Vladas Žukas (1925–2014), a Professor of Vilnius University, was one of the most significant researchers and participants in Lithuanian culture during a complicated part of the 20th century, specifically, the Soviet period. He was a highly recognised researcher of the humanities and social sciences in the Baltic region. High erudition, professional application of theoretical and methodological research tools, critical evaluation of research resources, along with well-grounded interpretation of historical sources were his distinguishing academic characteristics. He conducted productive studies of old writings, books and bibliography, while also expressing himself as a historian of culture. The results of these studies were embodied in academic courses of Lithuanian bibliography and theses; in total, Vladas Žukas wrote an impressive 28 books and monographs. The most important monographic works by V. Žukas form a continuous cycle of research publications. This cycle could be named “Lithuanian Book Culture and its Creators: Between Tradition and Innovation”. The dominant themes in these studies were: struggle for the public use of mother tongue, protection of the rights of the books in Lithuanian script during the times of oppression under the Russian Empire, issues pertaining to the advancement of press publishing and publishers in the independent Republic of Lithuania, the effect of book culture on the modernisation of society. V. Žukas supplemented his academic research by practicing his personal hobby of creating a unique collection of Lithuanian painters’ works. His guiding principle in tutoring students was to educate academically responsible and efficiently working specialists denoted by high professional competence. He was moderate, tactful and empathetic, while sometimes critical when assessing whether the knowledge acquired by the students in the course or the group is of the required level. Also, he was seen as a professionally insightful academician when evaluating the individual potential of his students. If the young people were struggling with personal issues, he was always the first to help overcome the problems by working more than formally required since he always was the one to walk the extra mile for the welfare of others.